2007
DOI: 10.17986/blm.2007121628
|View full text |Cite
|
Sign up to set email alerts
|

Giderek Artan Tehlike Kurusıkı Silahlar

Abstract: Blank cartridge guns can be altered as harmful handguns with a simple modification in their barrel. As a result, these guns may inflict serious and potentially life threatening injuries. In this study, it is aimed to draw attention to risks of blank cartridge guns of which use becoming more common.The records of the Council of the Forensic Medicine Adana Group Administration were used. Five cases of deaths due to modified blank cartridge guns injuries during the period of January 2006 and November 2006 were an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
(3 reference statements)
1
0
0
Order By: Relevance
“…In the literature, many of publications about blank gun injuries revealed that blank guns could be harmful for the soft tissue and the bone tissue. Our findings were consistent with the literature (1,(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). In present study, blank guns caused skin tissue damage, destruction of muscle tissue, burnings and the soot, frequently.…”
Section: Discussionsupporting
confidence: 93%
“…In the literature, many of publications about blank gun injuries revealed that blank guns could be harmful for the soft tissue and the bone tissue. Our findings were consistent with the literature (1,(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). In present study, blank guns caused skin tissue damage, destruction of muscle tissue, burnings and the soot, frequently.…”
Section: Discussionsupporting
confidence: 93%